Mapping instruments to assess and monitor the well-being and health of firefighters: Scoping review (Research, Society and Development, 2024)
The objective of this study was to identify and analyze instruments used to measure the physical and mental health and well-being of firefighters. Method: literature review, scoping review type, to support the process of evidence validation of a battery of instruments to identify and analyze the health and well-being of military firefighters, conducted in the following databases: PubMed, BIREME/Biblioteca Virtual em Saúde (BVS), SCOPUS, Web of Science, Lilacs. A search was also carried out in gray literature, with a time frame of 5 years and an advanced search strategy was applied with specific descriptors DeCS/MeSH and Emtree. Results: The results indicated that some studies such as Food frequency questionnaires developed and validated in Brazil: a scoping review protocol and Development and validation of the fire service safety climate scale, with approaches to the population segment and nature of the study, can support the choice of some concepts and instruments for the elaboration of a battery of instruments specific to firefighters. Final Considerations: The review highlights the need to develop more holistic instruments that contemplate the psychosocial factors and physical challenges unique to this profession.